41.3: A New Inspection and Review Solution with EFIB Accelerating the Yield Ramp of Display Panel Manufacturing. (26th August 2021) - Peng, Pai; Meng, Lin; Li, Lingjia; Geng, Tao; Mei, Xiaohan; Knaub, Nikolai; Shen, Lei; Li, Xiao; Wu, Chengye
Abstract : A new inspection and review solution has been introduced with the adoption of display industry's first inline EFIB (Electron Beam Review — Focused Ion Beam) system. Combined with AOI (auto optical inspection), Array tester and repair system, it provides critical information for failure analysis in a timely and cost‐effective manner. It has the capabilities of performing in‐depth and reliable failure analysis in active area, GOA (gate on array) and fanout area. In this paper, we present a number of EFIB applications during the yield ramp phase, demonstrating the value of this new solution in accelerating the yield ramp up process.